Interconversion type metal frame adsorption material with reversible structure as well as preparation method and application of interconversion type metal frame adsorption material

By controlling the activation temperature, the structure of MOFs material is transformed from one-dimensional to three-dimensional, and the structural reversibility is achieved through the solvothermal method, which solves the problems of irreversible structural structure and insufficient adsorption performance of existing MOFs materials in cadmium ion adsorption, and achieves efficient cadmium ion adsorption and material recycling.

CN119613759AActive Publication Date: 2025-03-14NANCHANG HANGKONG UNIVERSITY

Patent Information

Application Number
CN202510022444.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-14
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing MOFs materials have problems of irreversibility in cadmium ion adsorption and insufficient adsorption performance, which is difficult to effectively solve the problem of heavy metal pollution.

Method used

By controlling the activation temperature, the metal frame material can be transformed from a one-dimensional structure to a three-dimensional structure, and the material structure is reversibly restored by the solvothermal method, thereby optimizing the pore structure and adsorption performance.

Benefits of technology

The adsorption amount of cadmium ions is significantly improved, and the material structure is recyclable and regenerated, providing a new strategy for cadmium ion wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613759A_ABST
    Figure CN119613759A_ABST
Patent Text Reader

Abstract

The invention discloses a structure-reversible intervariant metal frame adsorption material and a preparation method and application thereof, and belongs to the technical field of adsorption materials, and the preparation method comprises the following steps: dissolving anhydrous calcium chloride and 2, 5-pyrazine dicarboxylic acid in a mixed solvent, then adding concentrated nitric acid, carrying out a heating reaction, continuing to activate the obtained solid product at 50-420 DEG C for 24 h, filtering, washing, and drying to obtain the structure-reversible intervariant metal frame adsorption material. And realizing structural transformation to obtain the intervariant metal frame adsorption material with the reversible structure. The reversible intervariant metal framework provided by the invention provides a new strategy for research and development of multifunctional MOFs materials, so that the material can adjust the pore characteristics and the three-dimensional space structure according to the temperature change, and the macroscopic adsorption performance is obviously influenced. The preparation process provided by the invention is simple and convenient, and a new strategy is provided for cadmium ion sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a structurally reversible interconversion type metal frame adsorption material and a preparation method and application thereof. Background Art

[0002] Metal Organic Frameworks (MOFs) are a new type of crystalline porous material formed by metal ions and organic ligands. Due to their inherent characteristics such as directional structural design and rich pores, they are widely used in ion adsorption, gas storage and separation, catalysis, drug delivery and sensing. Among this type of MOFs, materials that can respond to external environmental stimuli and achieve controllable transformation of microstructures have attracted much attention because they can exhibit unique macroscopic properties.

[0003] With the acceleration of industrialization, environmental pollution is becoming increasingly serious, especially the pollution of heavy metal ions such as cadmium, which not only destroys the ecosystem, but also seriously threatens human health. At present, adsorption has become an economical and efficient strategy for treating cadmium-containing wastewater. MOFs materials have been widely studied as a good adsorbent with adjustable structure. However, there are still many practical problems to be solved in the field of MOFs materials for the adsorption of cadmium ions.

[0004] Therefore, how to obtain a MOFs material that has good adsorption capacity for cadmium ions and whether the structure can be recycled is the focus of current technical personnel in this field. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a structurally reversible interconversion metal framework adsorption material and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a structurally reversible interconversion metal framework adsorption material comprises the following steps:

[0008] After dissolving anhydrous calcium chloride and 2,5-pyrazine dicarboxylic acid in a mixed solvent, concentrated nitric acid is added for heating reaction to generate a one-dimensional MOFs material (Ca-MOFs-1D). The obtained solid product is further activated at 50-420°C for 24 hours, and the coordination situation around calcium changes accordingly. At this time, the one-dimensional MOFs structure is transformed into a three-dimensional MOFs material (Ca-MOFs-3D) in the solid phase, and the structurally reversible interconvertible metal framework adsorption material is obtained.

[0009] Beneficial effects: The principle of achieving reversible transformation: As the activation temperature increases, the reduction of coordinated water molecules triggers the reorganization of the coordination structure, prompting the material structure to transform from one dimension to three dimensions. Reversibility can be achieved through solvothermal method: the material is redissolved in a mixed solvent, and the water molecules are re-coordinated to restore the material to its original structure while the original composition remains unchanged.

[0010] Preferably, the molar ratio of the anhydrous calcium chloride to 2,5-pyrazinedicarboxylic acid is 1:1.

[0011] Beneficial effect: The structure formed under this ratio is a one-dimensional structure.

[0012] Preferably, the mixed solvent is obtained by mixing N,N-dimethylacetamide (DMA) and water in a volume ratio of 2:1.

[0013] Beneficial effect: The one-dimensional material has the best crystal state under this solvent ratio.

[0014] Preferably, the volume ratio of the concentrated nitric acid to the mixed solvent is 100 μL:6 mL.

[0015] Beneficial effects: The addition of an appropriate amount of concentrated nitric acid helps the reaction proceed and promotes the formation of a coordination structure.

[0016] Preferably, the heating reaction is carried out at a temperature of 80° C. and for 48 hours.

[0017] Beneficial effect: The reaction temperature and reaction time make the crystallization state of the one-dimensional material reach the best.

[0018] Preferably, the activation temperature is 50°C, 60°C, 70°C, 80°C, 100°C, 140°C, 180°C, 220°C, 320°C or 420°C.

[0019] Beneficial effects: By exploring a series of activation temperatures, the optimal structural transformation conditions can be determined, thereby optimizing the pore structure of the material, improving its adsorption performance, and ensuring that the material can achieve the best effect in applications involving the adsorption of cadmium.

[0020] Preferably, the structural restoration of the structurally reversible interconvertible metal framework adsorption material comprises the following steps:

[0021] The structurally reversible interconversion metal framework adsorption material is dissolved in a mixed solvent, and then concentrated nitric acid is added to carry out a heating reaction. After the reaction is completed, the structural recovery of the structurally reversible interconversion metal framework adsorption material is completed.

[0022] Beneficial effects: The structurally reversible interconvertible metal framework adsorbent material can be restored from a three-dimensional structure to a one-dimensional structure by a solvothermal method, which proves the structural reversibility of the material.

[0023] A method for preparing a structurally reversible interconversion type metal framework adsorption material provides a structurally reversible interconversion type metal framework adsorption material.

[0024] Beneficial effects: The material can reversibly transform between one-dimensional and three-dimensional structures. This property enables the material to adjust its pore characteristics and three-dimensional spatial structure according to temperature changes, thereby significantly affecting its macroscopic adsorption performance.

[0025] Application of a structurally reversible interconvertible metal framework adsorption material in the adsorption of cadmium ions in water.

[0026] Preferably, the adsorption temperature is 35°C.

[0027] Beneficial effect: The adsorption effect is best at this adsorption temperature.

[0028] Compared with the prior art, the present invention has the following advantages and technical effects:

[0029] The present invention realizes the transformation of the metal framework material from a one-dimensional structure to a three-dimensional structure by precisely controlling the activation temperature. This structural change significantly optimizes the pore characteristics of the material, thereby increasing the adsorption of cadmium ions. The unique structural transformation characteristics of the metal framework material provided by the present invention provide a new strategy for the structural research of MOFs materials, allowing the material to adjust its pore characteristics according to temperature changes, significantly improving the macroscopic adsorption performance. In addition, the present invention restores the structure so that the structure of the material can be recycled. Finally, the preparation process provided by the present invention is simple, providing a new strategy for cadmium ion wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0031] Figure 1 This is a process flow chart for preparing the structurally reversible interconversion metal framework adsorption material of the present invention;

[0032] Figure 2 This is a SEM image of the material prepared in Example 2 with an activation temperature of 60°C;

[0033] Figure 3 This is a SEM image of the material prepared in Example 3 with an activation temperature of 70°C;

[0034] Figure 4 This is a SEM image of the material prepared in Example 4 with an activation temperature of 80°C;

[0035] Figure 5 This is the structure diagram of Ca-MOFs-1D;

[0036] Figure 6 This is the Ca-MOFs-3D structure diagram;

[0037] Figure 7 The PXRD patterns of the structurally reversible interconversion metal framework materials obtained in Examples 1-5 and 7;

[0038] Figure 8 This is a graph showing the adsorption capacity of cadmium ions by the structurally reversible interconvertible metal framework material obtained in Examples 1-10. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] The embodiment of the present invention provides a method for preparing a structurally reversible interconversion metal framework adsorption material, comprising the following steps:

[0042] After dissolving anhydrous calcium chloride and 2,5-pyrazine dicarboxylic acid in a mixed solvent, concentrated nitric acid is added for heating reaction to generate a one-dimensional MOFs material (Ca-MOFs-1D). The obtained solid product is further activated at 50-420°C for 24 hours, and the coordination situation around calcium changes accordingly. At this time, the one-dimensional MOFs structure is transformed into a three-dimensional MOFs material (Ca-MOFs-3D) in the solid phase, and the structurally reversible interconvertible metal framework adsorption material is obtained.

[0043] In a preferred embodiment, the molar ratio of anhydrous calcium chloride to 2,5-pyrazinedicarboxylic acid is 1:1.

[0044] In a preferred embodiment, the mixed solvent is a mixture of N,N-dimethylacetamide and water in a volume ratio of 2:1.

[0045] In a preferred embodiment, the volume ratio of the concentrated nitric acid to the mixed solvent is 100 μL:6 mL.

[0046] In a preferred embodiment, the heating reaction is carried out at a temperature of 80° C. and for a period of 48 hours.

[0047] In a preferred embodiment, the activation temperature is 50°C, 60°C, 70°C, 80°C, 100°C, 140°C, 180°C, 220°C, 320°C or 420°C. When the activation temperature is 80°C to 220°C, the prepared metal frame adsorption material has a large adsorption capacity for heavy metal ions. Therefore, in a preferred embodiment, in view of improving the adsorption effect and energy saving, the optimal activation temperature is 80°C.

[0048] In a preferred embodiment, the structural restoration of the structurally reversible interconvertible metal framework adsorption material comprises the following steps:

[0049] The structurally reversible interconversion metal framework adsorption material is dissolved in a mixed solvent, and then concentrated nitric acid is added to carry out a heating reaction. After the reaction is completed, the structural recovery of the structurally reversible interconversion metal framework adsorption material is completed.

[0050] The embodiment of the present invention also provides a method for preparing a structurally reversible interconversion type metal frame adsorption material and a structurally reversible interconversion type metal frame adsorption material prepared therefrom.

[0051] The embodiment of the present invention also provides an application of a structurally reversible interconversion metal framework adsorption material in adsorbing cadmium ions in water.

[0052] In a preferred embodiment, the adsorption temperature is 35°C.

[0053] In a preferred embodiment, the method specifically comprises the following steps:

[0054] The structurally reversible interconvertible metal framework adsorbent material is placed in a solution containing cadmium ions, and adsorbed by oscillation in a constant temperature water bath at a temperature of 35°C.

[0055] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0056] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0057] The concentration of concentrated nitric acid used in the following examples is 14.4-15.2 mol / L.

[0058] Example 1

[0059] A method for preparing a structurally reversible interconversion metal framework adsorption material, such as Figure 1 As shown, the following steps are included:

[0060] (1) DMA (4 mL) and H2O (2 mL) were added to a 10 mL sample bottle and ultrasonically mixed. 2,5-pyrazinedicarboxylic acid (16.8 mg, 0.1 mmol) and anhydrous calcium chloride (11.0 mg, 0.1 mmol) were weighed and added to the sample bottle. Concentrated nitric acid (100 μL) was added dropwise. The sample bottle was sealed with a cap and ultrasonically dispersed. The sample bottle was then placed in an 80 °C constant temperature oven and heated for 48 h. After cooling to room temperature, the product was filtered and washed with DMA and anhydrous ethanol. The obtained product was recorded as Ca-MOFs-1D. The structure is shown in the figure below. Figure 5 As shown, it was then placed in an oven at 50°C for activation for 24 hours to achieve structural transformation, and a white powdery metal framework adsorption material was obtained, which was recorded as Ca-MOF-50.

[0061] (2) Structural restoration: Take 20 mg of the material after structural transformation, add it to a mixed solvent of DMA (4 mL) and H2O (2 mL), add concentrated nitric acid (100 μL), seal it with a cap, and ultrasonicate it until it is completely dissolved. Then place the sample bottle in a constant temperature oven at 80°C and heat it for 48 hours. After cooling to room temperature, filter the product, and then wash it with DMA and anhydrous ethanol to achieve structural restoration.

[0062] Example 2

[0063] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 60° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-60.

[0064] Example 3

[0065] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 70° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-70.

[0066] Example 4

[0067] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 80° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-80.

[0068] Example 5

[0069] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 100° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-100.

[0070] Example 6

[0071] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 140° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-140.

[0072] Example 7

[0073] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 180° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-180.

[0074] Example 8

[0075] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 220° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-220.

[0076] Example 9

[0077] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 320° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-320.

[0078] Example 10

[0079] A method for preparing a structurally reversible interconvertible metal framework adsorption material, characterized in that the difference from Example 1 is that the activation temperature in step (1) is 420° C. The other process steps and parameters are the same as those in Example 1. The metal framework adsorption material obtained in step (1) is recorded as Ca-MOF-420.

[0080] Characterization Tests:

[0081] Characterization of the structurally reversible interconversion metal framework adsorption material obtained in Examples 1-10

[0082] 1. SEM analysis

[0083] The metal frame adsorption material obtained in Example 2-4 was selected for SEM characterization. The results are as follows: Figure 2-4 As shown, it can be observed that at an activation temperature of 60°C, the material maintains a complete crystalline morphology. As the activation temperature gradually increases, when the temperature reaches 70°C, slight cracks appear on the crystal surface. When the activation temperature is further increased to 80°C, the crystal fracture phenomenon becomes more obvious, the surface becomes rough, and the pores increase accordingly, indicating that the internal structure of the material has changed, which may affect its adsorption capacity.

[0084] 2. Powder X-ray diffraction analysis

[0085] The metal frame adsorption materials obtained in Examples 1-5 and 7 were selected for powder X-ray diffraction characterization. The results are as follows: Figure 7 As shown in the figure, as the activation temperature increases, the diffraction spectrum changes, indicating that the structure of the adsorbent material gradually changes. When the activation temperature is 80°C, its microstructure changes, and the subsequent single crystal structure data show that the material is completely transformed from a one-dimensional structure to a three-dimensional structure.

[0086] 3. Crystal parameter analysis

[0087] The metal framework adsorption material Ca-MOFs-1D obtained in step (1) of Example 1 and the Ca-MOFs-3D after the structural transformation at 80°C in Example 4 were selected for crystallographic analysis. The crystallographic data results are shown in Tables 1 and 2. Ca-MOFs-1D crystallizes in the monoclinic system with a space group of C2 / c. Its asymmetric unit contains a Ca 2+ , a deprotonated organic ligand and four water molecules. Among them, one Ca 2+ It coordinates with the nitrogen and carbonyl oxygen on the two pyrazine rings to form a five-membered ring, and extends repeatedly to form a one-dimensional chain structure similar to the "Heisenberg spin chain model" in the vertical direction. 2+ The remaining coordination sites are distributed laterally to the oxygens of four water molecules, which in turn keep the one-dimensional chain structure at a certain interval (e.g. Figure 5 As the temperature rises, due to Ca 2+ When the number of coordinated water is reduced to one, the crystal (Ca-MOFs-3D) changes from monoclinic to triclinic (space group is P-1). 2+ The coordination centers are close to each other to form an alternating structure of four-membered rings and five-membered rings. The chains are connected by organic ligands to form a three-dimensional structure and form certain cavity areas and channels (such as Figure 6 shown).

[0088] Table 1

[0089]

[0090]

[0091] Table 2

[0092]

[0093]

[0094] It can be seen from Tables 1 and 2 that after activation, the crystallographic data of the metal framework adsorption material changed, indicating that its crystal structure has undergone a transformation.

[0095] Application Example 1

[0096] The structurally reversible interconversion metal framework adsorption material obtained in Examples 1-10 is applied to the adsorption of cadmium ions, comprising the following steps:

[0097] Add 25 mg of the adsorbent material to an aqueous solution with a cadmium ion concentration of 500 mg / L, oscillate at a constant temperature of 35°C for 12 h, take the supernatant, filter it with a 0.22 μm microporous membrane, measure the cadmium ion concentration in the filtrate, and calculate the adsorption capacity. The adsorption capacity is as follows: Figure 8 As shown. With the increase of activation temperature, the adsorption effect of the prepared adsorbent material on cadmium ions is better, and the adsorption amount reaches the maximum and tends to be stable after 80℃. However, when the activation temperature is further increased from 220℃, the adsorption amount of cadmium ions by the prepared adsorbent material gradually decreases. Considering the adsorption effect and economy, the activation temperature of 80℃ is the best.

[0098] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a structurally reversible interconversion metal framework adsorption material, characterized in that: The following steps are involved: After anhydrous calcium chloride and 2,5-pyrazine dicarboxylic acid are dissolved in a mixed solvent, concentrated nitric acid is added for heating reaction, and the obtained solid product is activated at 50-420° C. for 24 hours to achieve structural transformation, thereby obtaining the structurally reversible interconversion metal framework adsorption material.

2. The method for preparing a structurally reversible interconversion metal framework adsorption material according to claim 1, characterized in that: The molar ratio of the anhydrous calcium chloride to 2,5-pyrazinedicarboxylic acid is 1:

1.

3. The method for preparing a structurally reversible interconversion metal framework adsorption material according to claim 1, characterized in that: The mixed solvent is obtained by mixing N,N-dimethylacetamide and water in a volume ratio of 2:

1.

4. The method for preparing a structurally reversible interconversion metal framework adsorption material according to claim 1, characterized in that: The volume ratio of the concentrated nitric acid to the mixed solvent is 100 μL:6 mL.

5. The method for preparing a structurally reversible interconversion metal framework adsorption material according to claim 1, characterized in that: The heating reaction was carried out at a temperature of 80° C. and for 48 hours.

6. The method for preparing a structurally reversible interconversion metal framework adsorption material according to claim 1, characterized in that: The activation temperature is 50°C, 60°C, 70°C, 80°C, 100°C, 140°C, 180°C, 220°C, 320°C or 420°C.

7. A method for preparing a structurally reversible interconversion metal framework adsorption material according to any one of claims 1 to 6, characterized in that: The structural restoration of the structurally reversible interconversion metal framework adsorption material comprises the following steps: The structurally reversible interconversion metal framework adsorption material is dissolved in a mixed solvent, and then concentrated nitric acid is added to carry out a heating reaction. After the reaction is completed, the structural recovery of the structurally reversible interconversion metal framework adsorption material is completed.

8. A structurally reversible interconvertible metal framework adsorption material prepared by the method for preparing a structurally reversible interconvertible metal framework adsorption material as described in any one of claims 1 to 7.

9. Use of the structurally reversible interconversion metal framework adsorption material as claimed in claim 8 in adsorbing cadmium ions in water.

Citation Information

Patent Citations

  • Dimming material composition and dimming device

    CN115477768A

  • Calcium-based metal organic framework material, preparation method thereof and application of calcium-based metal organic framework material in carbon dioxide trapping

    CN119219938A

Cited By

  • Calcium-based MOF (Metal Organic Framework) crystal material with photoelectric effect as well as preparation method and application of calcium-based MOF crystal material

    CN120424364A

  • A calcium-based MOF crystal material with photoelectric effect, its preparation method and application

    CN120424364B